Innovation process, innovation outcome and firm's performance in the Malaysian electrical and electronics industry - Suriati, Zainal Abidin (2014)
Innovation is vital in enhancing a firm’s performance and competitiveness. This study investigates the relationship between the antecedent variables (leadership, managerial levers and business processes), the innovation process and the firm’s performance. In addition, the study also examines the mediating effect of an innovation outcome on the relationship between the innovation process and firm’s performance. A total of 234 Malaysian electrical and electronics companies which are listed in the Federation of Malaysian Manufacturers 2012 were selected for this study. The data collection was obtained from the questionnaire surveys. The association between the variables was measured by depending on the extent of each company’s perception on innovation through the use of interval rating scale instruments. The Rasch Measurement Model was used for analysis and the data was then processed through the use of the Winstep Software. The results revealed that there were positive relationships between the antecedent variables and the innovation process, the innovation outcome and the firm’s performance. Further analysis through Rasch Measurement Model indicated a positive level of relationships between all three types of antecedents, innovation process, innovation outcome and the firm’s performance. The role of the innovation outcome as a mediating variable was then established. A higher probability of success in implementing the innovation process will result a higher ability level of innovation outcome. In addition, a higher ability level of innovation outcome will yield a higher firm performance. The results also revealed that the three groups of companies have performed according to their ability level (excellent, moderate and poor) when implementing innovation. Thus, companies with high ability will deliver high probability of successes in implementing innovation. The findings of this study will assist the companies in measuring their ability level when implementing a systematic innovation process in their respective organisations.